2008
DOI: 10.1158/1078-0432.ccr-07-4082
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Breast Cancer Metastases: Comparison of Therapeutic Target Expression and Promoter Methylation Between Primary Tumors and Their Multifocal Metastases

Abstract: Purpose: A comprehensive comparison of biomarker expression between patients' primary breast carcinoma (PBC) and their metastatic breast carcinomas (MBC) has not been done. Experimental Design: We did rapid autopsies (postmortem intervals,1-4 hours) on10 consenting patients who died of MBC.We constructed single-patient tissue microarrays from the patients' archived PBC and multiple different MBCs harvested at autopsy, which were immunohistochemically labeled for multiple biomarkers. Methylation of multiple gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(138 citation statements)
references
References 29 publications
(28 reference statements)
7
126
2
3
Order By: Relevance
“…Similar findings were reported by Wu et al (21) comparing the therapeutic target expression and promoter methylation between primary breast tumors and their multifocal metastases. Notably, the study showed that therapeutic targets identified in the primary breast tumors do not reflect targets present in the metastatic sites.…”
Section: Staining Intensity Score (% Cells) -------------------------supporting
confidence: 89%
“…Similar findings were reported by Wu et al (21) comparing the therapeutic target expression and promoter methylation between primary breast tumors and their multifocal metastases. Notably, the study showed that therapeutic targets identified in the primary breast tumors do not reflect targets present in the metastatic sites.…”
Section: Staining Intensity Score (% Cells) -------------------------supporting
confidence: 89%
“…Tumor cell heterogeneity has been observed in some series and could explain discordances in HER2 status between primary tumor and recurrence [25,26]. According to Wu et al primary tumors, as well as recurrences, are heterogeneous, with foci with variable morphology and marker expressions.…”
Section: Discussionmentioning
confidence: 99%
“…In metastatic breast cancer, it has been demonstrated that expression of estrogen/progesterone receptors and EGFR may be significantly different in metastatic lesions than in the primary tumor, which may impact therapeutic decisions. 37 In addition to this advanced disease setting, patients receiving neoadjuvant therapy may be good candidates for molecular testing of FNA samples. Such patients may demonstrate a complete pathologic response to the therapy upon surgical resection, with minimal or no residual tumor, placing increased importance on the molecular characterization of the initial biopsy.…”
Section: Molecularly Targeted Therapymentioning
confidence: 99%